1976
DOI: 10.1530/jrf.0.0470235
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary caffeine on the testis of the domestic fowl, Gallus domesticus

Abstract: Roosters were fed 0-1% caffeine mixed by weight into a standard ration. With continued dietary caffeine administration, the average fertility of eggs collected for 2 weeks from untreated pullets inseminated with semen from the treated males at 0, 7 and 14 days after the start of treatment was 30-8, 33-5 and 3-3%, respectively. After 14 days of treatment fertility was significantly lower (P less than 0-001) than before (0 days) or 7 days after treatment. Semen output and sperm concentration were markedly reduce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1981
1981
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…It is important to note that the weight of the testis is largely dependent on the mass of differentiated spermatogenic cells [38,39] and the weight of epididymis depends on the number of stored sperm in the epididymis. Caffeine seems to interfere with cell division resulting in a reduced number of spermatogenic cells [40,41]. As a result, the diameter of seminiferous tubules decreased significantly in offspring of both treatment groups during the prepubertal, postpubertal, and adulthood periods.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is important to note that the weight of the testis is largely dependent on the mass of differentiated spermatogenic cells [38,39] and the weight of epididymis depends on the number of stored sperm in the epididymis. Caffeine seems to interfere with cell division resulting in a reduced number of spermatogenic cells [40,41]. As a result, the diameter of seminiferous tubules decreased significantly in offspring of both treatment groups during the prepubertal, postpubertal, and adulthood periods.…”
Section: Discussionmentioning
confidence: 99%
“…Ax et al [40] showed that in the testes of roosters fed a diet containing 145 mg/kg caffeine for 35 days, the semen output and sperm concentration were markedly reduced 17 to 21 days after treatment, and no semen could be collected from the roosters after they had received caffeine for 30 days. Moreover, Margalioth et al [50] demonstrated that while exposure to caffeine enhanced sperm motility, the ability of the sperm to penetrate hamster oocytes was not improved.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, semen was collected and the samples were used for each experiment at the onset of examination, which was defined as time "0" for descriptive purposes, and 2, 3, and 4 weeks after TBP supplementation initiation as shown in Figure 1. The evaluation of sperm primarily occurred 2 weeks after the initiation of TBP dietary supplementation, because rooster spermatogenesis requires 12 to 13 days from the period of meiotic prophase until the sperm pass through the lumen of the seminiferous tubules (De Reviers, 1968;Ax et al, 1976).…”
Section: Animals and Sperm Preparationmentioning
confidence: 99%
“…Studies on the teratogenic or sperm-injuring potential of methylxanthine started nearly 40 years ago by investigating the effects of caffeine on spermatogenesis (Ax et al 1976). It is to note that all animal studies have demonstrated that, depending on the method of administration and the species, the developmental no-observedeffect level (NOEL) is approximately 30 mg/kg per day, the teratogenic NOEL is 100 mg/kg per day, and the reproductive NOEL approximately 80-120 mg/kg per day (Christian and Brent 2001).…”
Section: Methylxanthines and Spermatogenesismentioning
confidence: 99%